Implementation of Surgical Site Bundles in Reducing the Incident of Surgical Site Infections in Hospitals: A Systematic Review - Aris Mulyanto; Rusnoto Rusnoto; Blacius Dedi (Indonesian Journal of Global Health Research, 2026)
Surgical Site Infection (SSI) is a post-surgical complication that significantly contributes to increased morbidity, mortality, and hospital costs. The prevalence of SSI in Indonesia is reported to reach 2.3–18.3 % and is an important indicator of service quality. One effective prevention strategy is the implementation of a surgical site bundle, a collection of evidence-based interventions that must be implemented consistently. This article aims to systematically review empirical evidence regarding the effectiveness of implementing bundled surgical sites in reducing the incidence of SSI in hospitals. This study is a systematic review using the PRISMA protocol. Article searches were conducted through Google Scholar, Semantic Scholar, ProQuest, and ScienceDirect with publications spanning 2015–2025, Keywords used Surgical Site Bundle, Surgical Site Infection, compliance, hospital. Of the 1,285 articles found, eight articles met the inclusion criteria for analysis, covering quantitative, qualitative, and program evaluation designs related to the implementation of SSI bundles in hospitals. The review showed that bundle implementation was proven to reduce SSI rates. Studies in the United States reported a 30% reduction in SSIs in colorectal surgery, while in gynecologic oncology the incidence of SSIs decreased from 6% to 1.1%. Studies in Indonesia showed that bundle compliance was negatively associated with SSI rates (r = -0.502; p < 0.05 ) and that its implementation was able to shorten patient lengths of stay. However, the effectiveness of bundles is highly dependent on full compliance by healthcare workers and support from hospital management functions. Implementation of the surgical site bundle is effective in reducing SSI rates in hospitals, but its success is determined by consistent implementation, full adherence to the bundle elements, and management oversight. Efforts to improve education, audits, feedback, and patient engagement need to be strengthened to ensure sustainable implementation.